Simulation Of Check-In Passenger Flow For International Departure Due To Covid19 Situations - Ismail, Nur Azwahana (Universiti Sains Malaysia, 2022)
The airport is an important aspect of the air transportation system as it serves as a link between arrivals and departures. The global pandemic was declared on March 11th, 2020 by the World Health Organization (WHO) due to the rapid spread of COVID-19. The ongoing COVID-19 outbreak is one of the most serious global health crises of 2020 causing the aviation industry to face an unprecedented crisis. In this pandemic, the airport must effectively take a prevention to control the spread of COVID-19 and to adapt to the situation. Accordingly, this study aims to develop the check-in process of passenger flow for international departure due to COVID-19 situations. Two of the most crucial things to think about throughout this international departure process during the COVID-19 epidemic were the check-in counter and the self-service technology. This research was based on Kulim International Airport (KXP). WITNESS simulation software was used to propose the solution and to evaluate its performance and reliability. The result of labour efficiency shows that simulation models with the use of self-service technology and the lowest check-in counter and labour have the highest changes in labour efficiency with an increase of 12.80%. The result of the comparison of machine utilisation improvement shows that models with more basic elements have the lowest reduction with -21.67% for the kiosk, -5.44% for the economy counter, and -4.63% for the business class counter in busy percentage among other models.